Determinantes de la aceptación y uso del servicio de agua y saneamiento en el poblado Achuar de Pampa Hermosa, Trompeteros, Loreto. 2024 - Navarro Rucoba, Luz Maria (2024)
The study was carried out in the Achuar Indigenous Population Center of Pampa Hermosa. Trumpeters, in order to identify the determinants that affect the acceptance and use of water and sanitation services by residents. It is a non-experimental, descriptive, exploratory, analytical and transversal research. The sample was made up of 100% of residents who received the services made up of 50 structured surveys, with a Cronbach's Alpha reliability of 0.802. For data normality, the Shapiro Wilk test was used, which indicates that they do not follow a normal distribution. Therefore, the Rho Spearman statistical test was used, which allowed us to conclude; that the deeply rooted beliefs and customs of the Achuar community of Pampa Hermosa act as significant barriers to the adoption of hygiene and sanitation practices, perpetuating inadequate conditions; There is a lack of basic sanitation infrastructure and an efficient waste collection and treatment system, which negatively impacts their quality of life. Although there is widespread awareness of the importance of hygiene and sanitation for health, implementation of these practices is limited. The lack of consistency in the application of hygiene measures is evident and therefore the need to strengthen health education and ensure that interventions are culturally sensitive and adapted to local reality. The community expresses significant concern about the availability of drinking water, reflecting limitations in the distribution infrastructure and access to this essential resource. This finding highlights the urgency of developing strategies that ensure a constant and safe supply of water, combined with initiatives that promote the responsible and sustainable use of the resource.